Thermo-oxidative stabilization for natural rubber nanocomposites by polydopamine interfacial tailored clay. Issue 88 (7th September 2016) - Fu, Y.; Wang, L.; Zhang, L.; Wang, W.
Abstract : Bio-inspired interfacial tailored polydopamine improves the thermo-oxidative stabilization, aging resistance and mechanical properties of natural rubber via robust hydrogen bonding. Abstract : Polydopamine (PDA) is applied to natural rubber (NR)/clay nanocomposites through a facile dip-coating approach, which is inspired by the mussel adhesion proteins. This novel modification of clay perfectly captures the interfacial tailoring reinforcement principles for rubber/filler compounds. The hydrophilic PDA coating assists clay platelets to disperse uniformly in aqueous NR latex with respect to TEM observations. Furthermore, PDA modified montmorillonite (PDA-MMT) interacts with NR chains by robust hydrogen-bonding adhesion, which serves as an efficient physical cross-linker demonstrated with transverse magnetization decay analyses. The expectable enhancements are directly visualized in strengthened tensile properties with 46% increasement of tensile strength by adding 6 phr PDA-MMT and only 18% increasement without PDA modification. Besides, the E α →0 values of NR based composites follow such sequence: NR/MMT < NR < NR/PDA-MMT. Synthetic substitute of natural melanin as PDA is, PDA-MMT layers remarkably stabilize the NR matrix via radical-scavenging pathway during heat-treatment.